Valuasi Nilai Ekonomi Total dari Pemanfaatan Limbah B3 Slag Baja sebagai Bahan Pengerasan Jalan (incomplete) - Lydia Suwargana Putri; Iwan Juwana (Jurnal Serambi Engineering, 2021)
A common issue is that B3 steel slag waste produced by the iron and steel smelting industry is often dumped into the environment and can  lead to environmental pollution. The hazardous waste management that can be performed  is the use  of B3 steel slag waste as a road paving material. The method of analysis of this research is carried out based on the total economic value then a financial feasibility analysis is carried out using the concept of Cost Benefit Analysis (AMB). The purpose of this research is to identify and classify DUV, IUV, to perform a Total Economic Value assessment, and cost-benefit analysis. The result of the classification of the analysis of the total economic value of this research is the direct use value obtained for an  amount of Rp 2.504.943.750.000, an indirect usege value of Rp 11.285.686.875.000, and the total economic value of Rp 13.790.630.625.000. The Cost-Benefit Analysis (CBA) conducted in this study is financially feasible, because it meets the financial feasibility standards for a project with a NPV value of Rp 4.827.270.437.317, the Net BCR value of 7,78 and the Gross BCR value of 2,02, IRR of 154,2 %, and the Payback Periode of 4 months 3 days.